SARS-CoV-2 specific antibody trajectories in mothers and infants over two months following maternal infection - Martin, Melanie A.; Keith, Monica; Pace, Ryan M.; Williams, Janet E.; Ley, Sylvia H.; Barbosa-Leiker, Celestina; Caffé, Beatrice; Smith, Caroline B.; Kunkle, Amanda; Lackey, Kimberly A.; Navarrete, Alexandra D.; Pace, Christina D. W.; et al. (Frontiers in Immunology, 2022)
Infants exposed to caregivers infected with SARS-CoV-2 may have heightened infection risks relative to older children due to their more intensive care and feeding needs, and may experience more severe infection due to their less developed immune systems. However, there has been limited research on COVID-19 outcomes in exposed infants beyond the neonatal period. Between June 2020 – March 2021, we conducted interviews and collected capillary dried blood from SARS-CoV-2 infected mothers and their infants (aged 1-36 months) for up to two months following maternal infection onset (COVID+ group, 87% breastfeeding, n dyads = 46 dyads). Comparative data were also collected from breastfeeding mothers with no known SARS-CoV-2 infection or exposures (breastfeeding control group, n dyads = 26), and mothers who tested SARS-CoV-2 negative after experiencing symptoms or close contact exposure (COVID- group, n dyads = 11, 73% breastfeeding). Dried blood samples were assayed for anti-SARS-CoV-2 S-RBD IgG and IgA positivity and anti-SARS-CoV-2 S1 + S2 IgG concentrations. Within the COVID+ group, the mean probability of seropositivity among infant samples was significantly lower than that of corresponding maternal samples (IgG 0.54 vs. 0.87; IgA 0.33 vs. 0.85), with likelihood of infant infection positively associated with the number of maternal symptoms and other household infections reported. COVID+ mothers reported a lower incidence of COVID-19 symptoms among their infants as compared to themselves and other household adults, and infants had similar PCR positivity rates as other household children. No samples returned by COVID- mothers or their infants tested antibody positive. Among the breastfeeding control group, 44% of mothers but none of their infants tested antibody positive in at least one sample. Results support previous research demonstrating minimal risks to infants following maternal COVID-19 infection, including for breastfeeding infants.